Adaptive Smooth Multicast Protocol for Multimedia Transmission: Implementation Details and Performance Evaluation - Christos Bouras; Apostolos Gkamas; G Kioumourtzis (International Journal of Communication Systems, Wiley InterScience, 2010)
In this article we propose a new single-rate multicast congestion control scheme named Adaptive Smooth Multicast Protocol (ASMP), for multimedia transmission over best-effort networks. The smoothness lays in the calculation and adaptation of the transmission rate, which is based on dynamic estimations of protocols? parameters and dynamic adjustment of the “smoothness factor”, as well. ASMP key attributes are: a) TCP-friendly behavior, b) adaptive scalability to large sets of receivers, c) high bandwidth utilization, and finally d) smooth transmission rates, which are suitable for multimedia applications. We evaluate the performance of ASMP and investigate its behavior under various network conditions through extensive simulations conducted with the network simulator software (ns2). Simulation results show that ASMP can be regarded as a serious competitor of TFMCC and PGMCC. In many cases, ASMP outperforms TFMCC in terms of TCP-friendliness and smooth transmission rates, while PGMCC presents lower scalability than ASMP. We have implemented ASMP on top of RTP/RTCP protocols in ns2 by adding all the RTP/RTCP protocol?s attributes that are defined in RFC 3550 and related to QoS metrics.